Efficacy and safety of treatment simplification to atazanavir/ritonavir + lamivudine in HIV-infected patients with virological suppression: 144 week follow-up of the AtLaS pilot study. (26th February 2015) - Mondi, A.; Fabbiani, M.; Ciccarelli, N.; Colafigli, M.; D'Avino, A.; Borghetti, A.; Gagliardini, R.; Cauda, R.; De Luca, A.; Di Giambenedetto, S.
Abstract: Objectives: AtLaS was a single-arm pilot study that demonstrated promising efficacy and safety of treatment simplification to a dual regimen with atazanavir/ritonavir + lamivudine in virologically suppressed HIV-positive patients. Here, we report data from the 144 week follow-up. Methods: At baseline, patients treated with a three-drug atazanavir/ritonavir-based regimen were switched to 300/100 mg of atazanavir/ritonavir plus 300 mg of lamivudine once daily. Major clinical events, laboratory parameters, neurocognitive performance, bone composition and body fat distribution were monitored. Treatment failure was defined as a discontinuation/switch of the regimen or virological failure (HIV-RNA >50 copies/mL in two consecutive determinations or a single level above 1000 copies/mL). Results: After 144 weeks, 9/40 (22.5%) treatment failures occurred, including two virological failures (Weeks 48 and 53, without resistance). A significant increase in the CD4 count was observed at Week 96 (+124 cells/mm 3 ; P  = 0.002) and Week 144 (+94 cells/mm 3 ; P  = 0.008). After 144 weeks, a significant increase in total cholesterol (+25 mg/dL; P  = 0.001), HDL cholesterol (+6 mg/dL; P  = 0.024) and LDL cholesterol (+12 mg/dL; P  = 0.008) was observed, without any change in triglyceride levels, total cholesterol/HDL ratio or LDL/HDL ratio. A significant increase in the estimated glomerular filtration rate (+25 mL/min/1.73 m 2 ; P  < 0.001) and lumbar spine T -score and Z -score (+0.2, P  = 0.011; and +0.35, P  = 0.001, respectively) and a decrease in trunk fat (−1.898 g; P  = 0.005) were also observed. Neurocognitive function did not decline over time. Concerning safety, 10 moderate to severe adverse events were recorded in eight patients; overall seven cases of renal colic (possibly treatment related) were observed, leading to a discontinuation of treatment in two patients. Conclusions: Data from the 144 week follow-up suggested good long-term efficacy of the simplification strategy that was investigated, with rare virological failure and a potential for improvement of the CD4 count, renal function and bone mineral density. This strategy warrants further investigation in a randomized trial.